Case of Entamoebiasis in Pigs Raised with a Free Range Systems in Bali, Indonesia (KASUS ENTAMOEBIASIS PADA BABI YANG DIPELIHARA DENGAN CARA DIUMBAR DI BALI, INDONESIA) - Agustina, Kadek Karang; Dharmayudha, Anak Agung Gde Oka; Oka, Ida Bagus Made; Dwinata, I Made; Kardena, I Made; Dharmawan, Nyoman Sadra; Damriyasa, I Made (Jurnal Veteriner; Vol 17 No 4 (2016), 2017)
This research aims were to measure the prevalence of Entamoeba in pigs in Bali and to identify thezoonotic potential species of Entamoeba. A total of 183 pig stool samples from Bali have been examined.The method being used in this study were combination between coproscopy and molecular techniques.Concentration sedimentation with Sodium Acetic Formaldehide (SAF) as a solution was used in thecoproscopy method, while the Polimerase Chain Reaction method was used to amplify DNA of Entamoeba.Extracted sample’s DNA examined by using primers that specifically for Entamoeba: Entam 1 (F) (5’-GTTGAT CCT GCC AGT ATT ATA TG-3’) and Entam 2 (R) (5’-CAC TAT TGG AGC TGG AAT TAC-3), and toidentify the zoonotic potential species of Entamoeba, samples that produce 550 bp in first amplificationcontinued by primers Epolecki1 (F) (5’-TCG ATA TTT ATA TTG ATT CAA ATG-3’) and Epolecki2 (R) (5’-CCT TTC TCC TTT TTT TAT ATT AG-3’). The results showed that 76.6% of samples were positive incoproscopical examination, but 84.7 % produced 550 bp bands on PCR amplification by using generalprimers. All positive samples on the first PCR continued to second PCR used specific primers for E.poleckii as a potential zoonotic disease and all of the samples showed negative results. This datademonstrated that the prevalence of Entamoeba in a traditional pig scavenging systems in Bali was 84.7%but no specific infection infection caused by E. polecki was found.
Keywords: Entamoeba, pigs, Bali